2011
DOI: 10.1177/1077801210393923
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adaptation in Advocate Burnout: A Case of Good Soldiering

Abstract: Domestic violence and sexual assault advocates, unlike other social service workers, experience only moderate burnout. The present study extends burnout research, exploring simultaneous effects of job demands and adaptation factors as they relate to burnout in the advocacy population. The authors identify the good soldiering phenomenon in which advocates adapt to work that is worthwhile, but risky, demanding, and resource poor. Good soldiering is related to, but distinct from, a "calling" because it links to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…For instance, abortion clinic workers are drawn to the field because of their sympathetic position toward clients, and interactions with clients informs workers' understandings about their work (Joffe ). Similarly, Bemiller and Williams' () study of shelter advocates found that workers are motivated by committed passion and love of the job, rather than extrinsic benefits. Kolb (:22) refers to this as “moral wages,” or a “sense of satisfaction… (of) living up to the demands of their moral identity code, and the positive feelings that come with it.” Moral wages are potentially very important for low‐wage and voluntary helpers, as demonstrated through previous studies of welfare‐to‐work managers (Taylor, Turgeon, and Gross ), homeless shelter workers and volunteers (Rogers ), and victim advocates and counselors (Kolb , ).…”
Section: Moral Identity and Emotion In Human Service Workmentioning
confidence: 96%
“…For instance, abortion clinic workers are drawn to the field because of their sympathetic position toward clients, and interactions with clients informs workers' understandings about their work (Joffe ). Similarly, Bemiller and Williams' () study of shelter advocates found that workers are motivated by committed passion and love of the job, rather than extrinsic benefits. Kolb (:22) refers to this as “moral wages,” or a “sense of satisfaction… (of) living up to the demands of their moral identity code, and the positive feelings that come with it.” Moral wages are potentially very important for low‐wage and voluntary helpers, as demonstrated through previous studies of welfare‐to‐work managers (Taylor, Turgeon, and Gross ), homeless shelter workers and volunteers (Rogers ), and victim advocates and counselors (Kolb , ).…”
Section: Moral Identity and Emotion In Human Service Workmentioning
confidence: 96%
“…Currently, few studies conducted with domestic violence advocates inform the burnout literature (i.e., Baird & Jenkins, 2003;Baker, O'Brien, & Salahuddin, 2007;Bemiller & Williams, 2011;Brown & O'Brien, 1998;Jenkins & Baird, 2002). These studies have shown that job-related (i.e., work load, client exposure, stressors), interpersonal (i.e., social support availability), and demographic factors (i.e., age, counseling experience) are related to burnout symptoms.…”
Section: Burnout Among Domestic Violence Advocatesmentioning
confidence: 95%
“…However, while workers frequently recognize symptoms of vicarious trauma in others, they are unlikely to recognize them in themselves and may only see such training or intervention as reactive for those experiencing symptoms without further education (Bemiller and Williams, 2011). As Dahlberg and Krug (2002) mentioned, interventions at the individual level focus on education and skills training to promote attitudes, beliefs, and behaviors that hopefully will result in positive change.…”
Section: Recommendationsmentioning
confidence: 99%
“…Work with trauma survivors and the inherent sacrifice in the work of these professionals links them to other emotionally intense professions (Bemiller and Williams, 2011). Studies specific to GBV workers indicate that they experience changes in worldview, feelings of isolation, fear for clients' safety, feelings of powerlessness, confusion of rape and sex, tightening of personal boundaries, distrust, and feelings of personal vulnerability (Bemiller and Williams, 2011;Clemans, 2004). In particular, workers in the GBV field reported that their jobs increased their assertiveness, gave them greater control over their anger, and led to positive changes in their parenting skills (Ben-Porat and Itzhaky, 2009).…”
Section: Campus Gender-based Violence (Gbv) Professionalsmentioning
confidence: 99%
See 1 more Smart Citation